Rozwijanie kompetencji komputerowych i informacyjnych w glottodydaktyce na przykładzie podręczników do nauki języka angielskiego - Malinowski, Piotr J. (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The aim of the article is to present an analysis regarding the assessment of the application of information and communication technology (ICT) in conventional ELT coursebooks. The theoretical basis for the use of ICT in language learning and the presentation of the new core curriculum (CC) is followed by the study describing the way in which ICT tools are either integrated or ignored in current English textbooks. The study covered books used in the seventh grade of primary school (in line with the new CC). Six of the eight textbooks available on the market were selected for this purpose. The qualitative approach applied to this research comprised a thorough description and original evaluation of references to ICT. The prime factor determining the quality of the didactic materials in question was taking into consideration the opportunities to develop students’ digital skills through project work.
Keywords: podręcznik; język angielski; kompetencje TIK; coursebook; English; ICT; digital competences